Do Start-Up Subsidies for the Unemployed Affect Participants' Well-Being? A Rigorous Look at (Un-)Intended Consequences of Labor Market Policies - Marco Caliendo; Stefan Tübbicke (Institute of Labor Economics (IZA), 2019)
We estimate the long-term effects of start-up subsidies (SUS) for the unemployed on subjective outcome indicators of well-being, as measured by the participants' satisfaction in different domains. This extends previous analyses of the current German SUS program ("Gründungszuschuss") that focused on objective outcomes – such as employment and income – and allows us to make a more complete judgment about the overall effects of SUS at the individual level. This is especially important because subsidizing the transition into self-employment may have unintended adverse effects on participants' well-being due to its risky nature and lower social security protection, especially in the long run. Having access to linked administrative-survey data providing us with rich information on pre-treatment characteristics, we base our analysis on the conditional independence assumption and use propensity score matching to estimate causal effects within the potential outcomes framework. We find long-term positive effects on job satisfaction but negative effects on individuals' satisfaction with their social security situation. Further findings suggest that the negative effect on satisfaction with social security may be driven by negative effects on unemployment and retirement insurance coverage. Our heterogeneity analysis reveals substantial variation in effects across gender, age groups and skill levels. The sensitivity analyses show that these findings are highly robust.
Keywords: C14; L26; H43; I31; J68; 330; start-up subsidies; propensity score matching; counterfactual analysis; well-being